Corticosteroid, oseltamivir and delayed admission are independent risk factors for prolonged viral shedding in patients with Coronavirus Disease 2019. (13th August 2020) - Hu, Fuying; Yin, Gang; Chen, Youping; Song, Jiangqin; Ye, Maosong; Liu, Jie; Chen, Cuicui; Song, Yuanlin; Tang, Xinjun; Zhang, Yong
Abstract: Introduction: Coronavirus Disease 2019 (COVID‐19) has spread worldwide, and it has reached to more than 14.5 million cases. Although Hubei province is the epicenter of China, little is known about epidemiological and clinical features of COVID‐19 in other areas in Hubei province around Wuhan. In addition, the virological data, particularly the factors associated with viral shedding of COVID‐19 has not been well described. Objective: To describe the epidemiological and clinical features of patients with COVID‐19 in Tianmen city, and identify risk factors associated with prolonged viral shedding of COVID‐19. Methods: Inpatients with COVID‐19 admitted before February 9, 2020 were included. Characteristics were compared between patients with early and late viral RNA shedding. Multivariate cox regression model was used to investigate variables associated with prolonged viral shedding. Results: One hundred and eighty‐three patients were included. About 8.2% patients were categorized as critical degree of severity. All patients received antiviral therapy, with arbidol and interferon being the commonest. About 38.3% and 16.9% patients were treated with corticosteroid and immunoglobulin, respectively. Time from onset to admission (HR = 0.829, P  < 0.001), and administration of corticosteroid (HR = 0.496, P  = 0.002), arbidol (HR = 2.605, P  = 0.008) and oseltamivir (HR = 0.416, P  < 0.001) were independently associated with duration of viral shedding. Conclusion: Symptoms of patients from Tianmen are relatively mild. Treatment should be started as early as possible, but corticosteroid and oseltamivir should be initiated with caution. In addition, clinical trials on arbidol should be conducted to demonstrate its effectiveness.